Comprensión lectora en alumnos de 6° grado de instituciones educativas estatales del distrito del Callao - Rojas Guevara, Martha Lucía (2012)
The research aims to describe the level of reading comprehension of sixth grade students from Callao stales institutions. We used a simple descriptive design, evaluating a probabilistic sample available of 128 children, aged 10 to 12 years from 3 schools. Were evaluated with reading comprehension test ACL 6 created by Catalá Catalá Monclús and Molina (2001) adapted by Ortega and Ramirez (2009). The study concluded that students show low performance in reading comprehension Also the results found in each literal dimensions, reorganizacional, inferential and criterial was low.